Holistic security in a fragmented governance structure, 1998-2003 - Winn, Neil (UK Data Service, 2008)
This study contains two datasets which provide a complete overview of all European Union (EU) Justice and Home Affairs (JHA) and Common Foreign and Security Policy (CFSP) joint actions between 1998-2003. Two datasets have been constructed using the electronic portal to EU law, EUR-Lex, to consult online editions of the Official Journal of the European Union (L series). Every edition of the Official Journal between 1998 and 2003 was browsed by year. Subsequently, all ‘joint actions’, ‘decisions’ and ‘framework decisions’ relating to CFSP and JHA were printed, filed, sorted and analysed, and relevant information from these was extracted and entered into the datasets under the appropriate headings. This process made it possible to see all data at a glance in comparative tables, whereas, previously, it was only possible to gather data by looking up the details of each action separately in the Official Journal of the European Union. The datasets provide a useful resource and a basis for further research in this area.